1993
DOI: 10.1111/j.2042-7158.1993.tb05662.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Depolarizing and Direct Current Systems on Iontophoretic Enhancement of Transport of Sodium Benzoate Through Human and Hairless Rat Skin

Abstract: A direct current (DC) system and a pulsed depolarization (PD) system were evaluated for their iontophoretic permeation of sodium benzoate, as a model drug, through hairless rat and human skin. Approximately the same initial permeation of sodium benzoate through the hairless rat skin was obtained at 0.1 mA for the DC device and at 3.0 mA for the PD device. Study of the drug's permeation was performed using a two-chamber iontophoretic diffusion cell, over two cycles of three successive on-off experimental condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…5) Since an optimal iontophoretic effect requires maximal ionization, 6,7) effective drug transport must minimize pH changes in the drug-containing solution. In order to overcome these disadvantages, systems using a silver or silver-silver chloride electrode 8,9) or pulsed direct current 10) have been investigated. However, there have been few reports demonstrating both safety and drug availability when iontophoretic systems were used in vivo.…”
mentioning
confidence: 99%
“…5) Since an optimal iontophoretic effect requires maximal ionization, 6,7) effective drug transport must minimize pH changes in the drug-containing solution. In order to overcome these disadvantages, systems using a silver or silver-silver chloride electrode 8,9) or pulsed direct current 10) have been investigated. However, there have been few reports demonstrating both safety and drug availability when iontophoretic systems were used in vivo.…”
mentioning
confidence: 99%
“…Numajiri et al compared the percutaneous absorption of sodium benzoate between direct current (DC) (0.1 mA/cm 2 ) and PDC (3 mA/cm 2 , rectangular waveform, 40 kHz and 30% duty cycle). 5) They reported that the amount of drug absorbed was almost equal and PDC was more suitable in terms of skin irritation. Zakzewski et al 6) and Bagniefski et al 7) also showed an equivalent absorption between DC and PDC.…”
mentioning
confidence: 99%
“…There are reports on the efficiency in the substances delivery through the skin by pulsed direct current (PDC), without causing burning and discomfort risk when compared to CDC. On the other hand, some authors have found greater, smaller or equal efficacy between CDC and PDC for substances delivery into the skin by iontophoresis [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%